2008
DOI: 10.1021/ja801169j
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Characterization of a Reaction Intermediate in Carbapenem Hydrolysis by B. cereus Metallo-β-lactamase

Abstract: Metallo-β-lactamases hydrolyze most β-lactam antibiotics. The lack of a successful inhibitor for them is related to the previous failure to characterize a reaction intermediate with a clinically useful substrate. Stopped-flow experiments together with rapid freeze-quench EPR and Raman spectroscopies were used to characterize the reaction of Co(II)-BcII with imipenem. These studies show that Co(II)-BcII is able to hydrolyze imipenem both in the mono- and dinuclear forms. In contrast to the situation met for pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(138 citation statements)
references
References 52 publications
11
127
0
Order By: Relevance
“…The effect of this mutation on the rate-limiting step of the reaction allows us to propose a strategy for designing a mechanism-based inhibitor with an evolutionary perspective. Recent mechanistic studies suggest that intermediate stabilization by the Zn2 site is essential in M␤L catalysis (33,34). Our results show that optimization of the chemistry in the active site can still be optimized by better positioning Zn2.…”
Section: Discussionmentioning
confidence: 64%
“…The effect of this mutation on the rate-limiting step of the reaction allows us to propose a strategy for designing a mechanism-based inhibitor with an evolutionary perspective. Recent mechanistic studies suggest that intermediate stabilization by the Zn2 site is essential in M␤L catalysis (33,34). Our results show that optimization of the chemistry in the active site can still be optimized by better positioning Zn2.…”
Section: Discussionmentioning
confidence: 64%
“…Although nitrocefin is not a clinically useful antibiotic, its usefulness as a probe of the catalytic mechanism of M␤Ls should not be underestimated. It has been shown recently that carbapenem hydrolysis by a B1 M␤L also proceeds by means of an anionic intermediate, after C-N bond cleavage (58). This evidence points to a general role of the Zn(II) ion in the DCH/DHH site of M␤L from all subclasses, which may be targeted as a common mechanistic element for inhibitor design.…”
Section: Discussionmentioning
confidence: 93%
“…This fact highlights its amazing chemical versatility. In the case of M␤Ls, the Zn(II) ion is able to contribute to ␤-lactam hydrolysis by 1) lowering the pK a of a bound water molecule, which may act as a nucleophile, providing a high local concentration of hydroxide ions at neutral pH (37,57); 2) acting as a Lewis acid, polarizing the CϭO bond and therefore augmenting the electrophilic nature of the carbonyl carbon (57); and 3) stabilizing a negative charge in the bridging nitrogen of the lactam moiety, after C-N bond cleavage (16,17,24,36,58,59). These three roles have been invoked for the two metal binding sites in M␤Ls, but it is not clear yet which of them are essential for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite steady-state kinetic studies at different pH values (54) suggesting the requirement of two bound metal ions for the hydrolytic activity of the B1 M␤L BcII, it has been recently shown that BcII can be active as a mono-zinc species with the metal ion accommodated at the Zn2 site, i.e. resembling the conformation of the B2 active site (55,56). Recent studies have revealed that the B3 lactamase GOB (57) is able to act as a mononuclear enzyme with the metal ion in the putative Zn2 site, i.e.…”
Section: Mechanistic Comparison Between B1 and B2 M␤lsmentioning
confidence: 99%